2013
DOI: 10.1021/ic401310c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Figure of Merit in Stannite–Kuramite Solid Solutions Cu2+xFe1–xSnS4–y (x = 0–1) with Anisotropy Lowering

Abstract: In this Article, we elucidate the structural and thermoelectric properties of stannite-kuramite solid solutions, Cu(2+x)Fe(1-x)SnS(4-y) (x = 0-1), with sulfur defects (y) ≤ 0.4. Structural analysis revealed that anisotropy decreases and Cu/Sn disorder increases with an increase in x. The samples with x = 0.8-1 exhibit degenerate conduction, whereas the Seebeck coefficient (S) remains relatively high, S ≈ 100 μV K(-1) for x = 0.8 at 300 K. Thermal conductivities (κ) of the solid solutions are in the range 10(-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Introducing vacancies is another practical way for the electrical transport optimization as well as the lattice thermal conductivity minimizing. Cu vacancy is the most common for p-type doping such as Cu 1−x In(Ga)Te 2 [87,124] and Cu 3−x SbSe 4 [125], which is due to the small formation energy of this defect, while anion vacancies are feasible for donor doping as seen in CuFeS 2−x [74] and Cu 2 FeSnS 4−x [126].…”
Section: Tetragonal Diamond-like Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing vacancies is another practical way for the electrical transport optimization as well as the lattice thermal conductivity minimizing. Cu vacancy is the most common for p-type doping such as Cu 1−x In(Ga)Te 2 [87,124] and Cu 3−x SbSe 4 [125], which is due to the small formation energy of this defect, while anion vacancies are feasible for donor doping as seen in CuFeS 2−x [74] and Cu 2 FeSnS 4−x [126].…”
Section: Tetragonal Diamond-like Compoundsmentioning
confidence: 99%
“…12a. It can be qualitatively utilized as an indicator map to discover or optimize high-performance tetragonal dia- Figure 12 (a) Distortion parameter as a function of the lattice parameter a [28,72,87,[106][107][108]119,123,126,136,137]. (b) Temperature dependence of zT for tetragonal diamond-like compounds [28,29,87,112,119].…”
Section: Tetragonal Diamond-like Compoundsmentioning
confidence: 99%
“…Not just chalcopyrite type quaternary chalcogenides, but the other structural forms of these quaternary chalcogenides such as wurtzite, orthorhombic, stannite and stannite‐kuramite etc. have been explored in the recent times ,,,. There is a possibility that random distribution of cations and anions in the unit cell gave rise to structural anisotropy which is responsible for lowering thermal conductivity in such material.…”
Section: Thermoelectric Applicationsmentioning
confidence: 99%
“…The scaled‐up synthesis procedures and versatile techniques have been established to further reduce the cost function for its effective commercial PV realization ,,. Interestingly, huge range of Cu‐based quaternary chalcogenide Cu 2 M I M II X 4 (where, M I =Zn, Ni, Co, Fe, Mn, Cd and Hg; M II =Si, Sn and Ge and X=S and/or Se) materials have been emerged in the recent time claiming vivid application of these material in diverse fields ,,,. This review presents the key features and recent developments in the direction of synthesis and multifunctional applications of these Cu‐based quaternary chalcogenides.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ZT values obtained for these are still about 0.9, these are still lower than those for ternary compounds. It has been reported that for quaternary materials, relatively low thermal conductivity and good electrical properties could be achieved by appropriate doping [21][22][23][24]. It has been reported by various workers that modification of electrically conducting units by doping of Cu 2+ create more hole carriers and extra conducting pathways [25][26][27].…”
Section: Introductionmentioning
confidence: 99%